1994
DOI: 10.1108/09534819410056087
|View full text |Cite
|
Sign up to set email alerts
|

Beyond TQM Programmes

Abstract: The failure rate of TQM interventions exceeds 75 per cent. Contends that it is missteps in the implementation of TQM – and other associated change efforts such as process re‐engineering – that undermine the likelihood that the intervention will contribute in a significant and lasting way to the competitive effectiveness of the organization. Using three case examples of TQM efforts, suggests that the implementation process must succeed in unhooking the organization from its traditional hierarchical and function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 1 publication
2
38
0
1
Order By: Relevance
“…Specifically in the context of quality improvement Spector and Beer [25] propose the following steps.…”
Section: Organizations In Changementioning
confidence: 99%
See 1 more Smart Citation
“…Specifically in the context of quality improvement Spector and Beer [25] propose the following steps.…”
Section: Organizations In Changementioning
confidence: 99%
“…Maybe here the SPI literature could benefit from ideas presented in organizational learning on methods for advancing learning, such as in Fig. 1., and quality improvement steps proposed by [25].…”
Section: Learningmentioning
confidence: 99%
“…Therefore, bearing in mind that experience has shown that some firms fail when they implement TQM (Boje and Winsor, 1993;Spector and Beer, 1994) and the implementation of TQM cannot be successful without the use of suitable quality management methods (Sitkin, Sutcliffe and Schoroeder, 1994;Wilkinson et al, 1998;Zhang, 2000) such as statistical techniques (Stuart, Mullins and Drew, 1996), managers of ISO 9000-certified small and medium firms that really want to progress towards a TQM culture, should implement the following factors, using the following methods: − Specialized training. Training cannot stop at an initial level, and must be of a continued nature (Ishikawa, 1985).…”
Section: Implications For Managersmentioning
confidence: 99%
“…An analogous problem has been identified in the TQM literature where management dedication and visible efforts to implement new routines are often emphasized. The failure rate for TQM efforts is high, and, according to Spector and Beer (1994), most of these failures can be attributed to management's half-hearted dedication and not having fully understood the dynamics of organizational change they are attempting to unleash. Some caution is needed in relation to this analogy since there are significant differences between IC and TQM.…”
Section: The Development Of Sohsm In Norwaymentioning
confidence: 99%